The Baltic Health Index (BHI): Assessing the social–ecological status of the Baltic Sea. Issue 2 (19th January 2021) - Blenckner, Thorsten; Möllmann, Christian; Stewart Lowndes, Julia; Griffiths, Jennifer R.; Campbell, Eleanore; De Cervo, Andrea; Belgrano, Andrea; Boström, Christoffer; Fleming, Vivi; Frazier, Melanie; Neuenfeldt, Stefan; Niiranen, Susa; et al.
Abstract: Improving the health of coastal and open sea marine ecosystems represents a substantial challenge for sustainable marine resource management, since it requires balancing human benefits and impacts on the ocean. This challenge is often exacerbated by incomplete knowledge and lack of tools that measure ocean and coastal ecosystem health in a way that allows consistent monitoring of progress towards predefined management targets. The lack of such tools often limits capabilities to enact and enforce effective governance. We introduce the Baltic Health Index (BHI) as a transparent, collaborative and repeatable assessment tool. The Index complements existing, more ecological‐oriented, approaches by including a human dimension on the status of the Baltic Sea, an ecosystem impacted by multiple anthropogenic pressures and governed by a multitude of comprehensive national and international policies. Using a large amount of social–ecological data available, we assessed the health of the Baltic Sea for nine goals that represent the status towards set targets, for example, clean waters, biodiversity, food provision, natural products extraction and tourism. Our results indicate that the overall health of the Baltic Sea is suboptimal (a score of 76 out of 100), and a substantial effort is required to reach the management objectives and associated targets. Subregionally, the lowest BHI scores were measured for carbon storage, contaminants and lasting special places (i.e. marine protected areas), albeit with large spatial variation. Overall, the likely future status of all goals in the BHI averaged for the entire Baltic Sea is better than the present status, indicating a positive trend towards a healthier Baltic Sea. However, in some Baltic Sea basins, the trend for specific goals was decreasing, highlighting locations and issues that should be the focus of management priorities. The BHI outcomes can be used to identify both pan‐Baltic and subregional scale management priorities and to illustrate the interconnectedness between goals linked by cumulative pressures. Hence, the information provided by the BHI tool and its further development will contribute towards the fulfilment of the UN Agenda 2030 and its Sustainability Development Goals. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.